1986
DOI: 10.1136/jnnp.49.7.749
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of Creutzfeldt-Jakob disease in England and Wales 1970-1979. II: Epidemiology.

Abstract: A comprehensive search yielded 121 confirmed cases of Creutzfeldt-Jakob disease who died in England and Wales in the decade 1970-1979, 31 probable cases and 10 possible cases. Descriptive epidemiological data are presented. The average annual incidence was 0 3 cases/million. An unexpected female excess was found. There was no evidence of space-time clustering of cases and no associations with occupation or past medical treatment were apparent. There was statistically significant variation in incidence rates in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
3
2

Year Published

1991
1991
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(24 citation statements)
references
References 13 publications
3
16
3
2
Order By: Relevance
“…The overall incidences remained in the range between 0.5 and 0.6 per million person year. And the incidence of patients with CJD onset after 80 years of age was still high without sharply decline, which was different from previous reports of other countries [20,21,[26][27][28]. The genetic study of the codon 129 of the PRNP genotype revealed that our patients were all Met/Met methionine homozygous instead of heterozygous.…”
Section: Discussioncontrasting
confidence: 83%
“…The overall incidences remained in the range between 0.5 and 0.6 per million person year. And the incidence of patients with CJD onset after 80 years of age was still high without sharply decline, which was different from previous reports of other countries [20,21,[26][27][28]. The genetic study of the codon 129 of the PRNP genotype revealed that our patients were all Met/Met methionine homozygous instead of heterozygous.…”
Section: Discussioncontrasting
confidence: 83%
“…Age specific incidence rates, with the majority of cases in the 60-75 year age group, are consistent in national surveys, but the previously described female excess of cases in England and Wales (26,11) has been maintained in the current study. This female preponderance, also described in some other countries, is unexplained.…”
Section: Epidemiology Of Cjd In England Andsupporting
confidence: 56%
“…Significant variations in CJD case rates were noted previously in France and in England (3,4,18,19). As possible explanations, ethnic compositions, environmental factors, case finding artifacts or case-to case transmisssion as a less probable eventuality, have been suggested (17).…”
Section: Resultsmentioning
confidence: 86%
“…Detailed statistical studies have been performed on CJD focal occurrence (2,3,10,17). Apart from familial CJD clustering, no statistically significant temporospatial relationships have been demonstrated up to now (4,18).…”
Section: Introductionmentioning
confidence: 99%